Global Isomeric Survey of Elusive Cyclopropanetrione: Unknown but Viable Isomers - Xin, Jing-fan; Han, Xiao-ru; He, Fei-fei; Ding, Yi-hong (Frontiers in Chemistry, 2019)
Despite the great interest in energy storage application, stable neutral CnOn (n > 1) structures either in thermodynamics or kinetics have yet been largely limited due to the rather high tendency to release the very stable CO molecule. The neutral cyclopropanetrione (C3O3) cluster has long remained elusive since no isomer with sufficient kinetic stability has been found either experimentally or theoretically. In this work, we constructed the first global potential energy surface of singlet C3O3 at the CCSD(T)/aug-cc-pVTZ//B3LYP/aug-cc-pVTZ level, from which the kinetic stability of a wide range of C3O3 isomers can be determined by investigating their isomerization and fragmentation pathways. Amongst, a three-membered ring structure 01 is the global C3O3 isomer with a barrier of 10.6 kcal/mol at the sophisticated W1BD level. In particular, two carbene-type isomers 02 and 04 possess appreciable destruction barriers of 20.3 and 24.7 kcal/mol at W1BD, respectively. Thus, 02 and 04 can be useful building blocks for constructing larger high-energy density carbon-oxygen clusters. Moreover, with the carbene center, both might effectively functionalize various nano-materials while retaining the electrochemical active carbonyl and epoxyl moieties that are very desirable in alkali metal-ion batteries.